Tuning thermal properties and biodegradability of poly(isosorbide azelate) by compositional control through copolymerization with 2, 5-furandicarboxylic acid. (January 2022) - Kasmi, Nejib; Terzopoulou, Zoi; Chebbi, Yosra; Dieden, Reiner; Habibi, Youssef; Bikiaris, Dimitrios N.
Highlights: Novel fully biobased poly(isosorbide azelate) homopolyester (PISAz) and ​poly(isosorbide furanoate-co-azelate) (PISFAz) copolyesters series were synthesized for first time. The controlled incorporation of 2, 5-furandicarboxylic acid moiety (FDCA) into polyester backbone proved to be a very efficient route to enhance the thermal properties of PISFAz. PISFAz copolyesters with tunable Tg over a high and broad temperature window oscillating from 9 to 91 °C depending on FDCA content (vs . Tg of −3 °C for PISAz). All FDCA-based copolyesters showed enhanced susceptibility to enzymatic degradation with a weight loss in the 25–61% range after 30 days (vs . only 13% for PISAz). Abstract: A new fully biobased poly(isosorbide furanoate-co-azelate) (PISFAz) copolyester series was synthesized through melt polycondensation. Incorporation of 2, 5-furandicarboxylic acid (FDCA), a rigid comonomer, at different molar ratios in poly(isosorbide-azelate) homopolymer led to tuning of the thermal properties and biodegradability of the resulting copolyesters. The PISFAz copolyesters with various FDCA molar content spanning from 10 to 70% were prepared and characterized by FTIR, GPC, 1D/2D NMR and viscosity measurements. It was found that PISFAz were totally amorphous materials with high thermal stability. NMR results indicated that random microstructures were obtained for the prepared copolymers with high azelaic acid content (⩾ 60 mol%). Most notably, the inclusion of FDCA units into the copolymer molecular chains induced a significant increase in the glass transition temperatures (Tg ) that varied from 9.2 to 91.1 °C depending on FDCA content, leading to copolyesters with tunable Tg over a wide temperature window. The enzymatic hydrolysis behavior of PISFAz was assessed using lipases from Pseudomonas cepacia and Rhizopus oryzae revealing different susceptibility to enzymatic attack depending on the comonomer ratio, with a maximum degradation rate up to 61% after 30 days. These novel furanoate-based copolyesters show great potential to serve as promising green thermoplastic materials for applications requiring high Tg values. Graphical abstract: Image, graphical abstract